Identification of zygotic trifoliate orange seedlings with RAPD molecular markers - Schäfer, Gilmar; Bastianel, Marinês; Dornelles, Ana Lúcia Cunha (Pesquisa Agropecuaria Brasileira, 2004)
This work aimed to determine germination frequency of zygotic embryos of seeds originated from open pollinated trifoliate orange [Poncirus trifoliata (L.) Raf.], using RAPD molecular markers. Leaves and seeds of P. trifoliata were collected from five commercial nurseries and from a citrus germplasm collection. The seeds were placed to germinate in plastic tubes in a greenhouse, reaching a final sample of 62 seedlings. Nine primers were used and the band patterns generated from seedlings leaves were compared to progenitor-plant-leaf hands. It was possible to identify 3.23% of seedlings originated from zygotic embryos which is acceptable in propagation by seeds in this rootstock.
Keywords: Poncirus trifoliata; rootstocks; citrus; embryo